2012
DOI: 10.1063/1.4753798
|View full text |Cite
|
Sign up to set email alerts
|

Polarized and diameter-dependent Raman scattering from individual aluminum nitride nanowires: The antenna and cavity effects

Abstract: Raman scattering of individual aluminum nitride (AlN) nanowires is investigated systematically. The axial direction of single nanowire can be rapidly verified by polarized Raman scattering. The angular dependencies of E-2(high) mode show strongly anisotropic behavior in smaller nanowires, which results from optical antenna effect. Raman enhancement (RE) per unit volume of E-2(high) increases with decreasing diameter of nanowires. Compared to the thin film, similar to 200-fold increase of RE is observed in AlN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…Concerning NWs with wurtzite crystal structure, a detailed analysis of phonon symmetries was performed on GaN NWs by Livneh et al 73, although they did not observe an anisotropy in the Raman intensity linked to the antenna effect. This enhancement was later observed in GaN 70, AlN 74 and InAs 34 NWs with the wurtzite structure.…”
Section: Single Nanowiresmentioning
confidence: 70%
“…Concerning NWs with wurtzite crystal structure, a detailed analysis of phonon symmetries was performed on GaN NWs by Livneh et al 73, although they did not observe an anisotropy in the Raman intensity linked to the antenna effect. This enhancement was later observed in GaN 70, AlN 74 and InAs 34 NWs with the wurtzite structure.…”
Section: Single Nanowiresmentioning
confidence: 70%
“…The charge related parameters are given in Table A1 while the bond-order and pairwise parameters are given in Table A2. 3.10166 6.209731 J (eVe -1 ) 2 3.53243 9.29225 K (eVe -1 ) 3 0.48166 -1.25446 L (eVe -1 ) 4 0.0 0.286350 ξ (Ặ -1 )…”
Section: Appendixmentioning
confidence: 99%
“…Aluminum nitride (AlN) is an important III-V semiconductor material due to its wide band gap, high thermal conductivity, low thermal expansion, and non-toxicity [1]. Nanostructures of AlN are used for field emitters in flat panel displays [2] and photo-detectors [3,4]. Additionally, thin films of AlN and aluminum oxynitride are important engineering protective coatings [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al [19] performed a finite difference time domain simulation of the same problem, showing again that the electric field inside the NW is distributed in a nonhomogeneous and localized manner which depends on its diameter. In general, these calculations of the effect of substrate type and NW geometry on Raman line intensity are performed assuming a two-dimensional geometry, based on the fact that the NW length can be assumed infinite as compared to their diameter [19,22,[24][25][26]. In addition to this effect of a substrate and of the specific NW diameter, it was also shown that the laser beam wavelength has a strong influence on Raman line intensities measured in semiconductor NWs [19,25,27].…”
Section: Contributedmentioning
confidence: 99%
“…In addition to this effect of a substrate and of the specific NW diameter, it was also shown that the laser beam wavelength has a strong influence on Raman line intensities measured in semiconductor NWs [19,25,27]. Finally, laser beam polarization is also important, in general the measurements are performed with the electric field of the laser beam polarised along the NW axis [19,22,23,26,28,29].…”
Section: Contributedmentioning
confidence: 99%